(untitled) (Bangladesh Journal of Bioethics, 2019)
Bangladesh Bioethics Society (BBS) is inviting all National and International individuals and institutions from any discipline those who are interessted in bioethicsto to become a member of BBS . Bioethics is interdisciplinary study of philosophical, ethical, social, legal, medical, ethnological, environmental, economic, therapeutic, religious, and other related issues arising from biological sciences and technologies, and their applications in human society and the biosphere. Membership Benefits: • Leadership Opportunities: Hold elective committee / Subcommittee of BBS • Voting right: Right to vote in BBS election. • Networking: Be listed in and access online BBS member directory. • Free Journal Subscription • Access to attend bioethical meetings/ conferences/ seminars/ workshops on bioethics in county and abroad. • Access to attend in research / training on bioethics. • Access to attend Annual General Meeting • Receiving the Societies Newsletters and other mailings concerning Society activities. • Get priority for registration waiver, free accommodation and meals during conferences/ Seminars of BBS, in some cases travel grants. • Reviews articles for the Journal and would be invited for lecture, book writing etc Please contact to Bangladesh Bioethics Society